Initial Handling by Midwives for Febrile Seizures in Children in the Working Area of Barus Jahe Health Center, Barus Jahe District Karo Regency, North Sumatra Province in 2023 - Sri Muliana Putri Bakara; Juliana Munthe; Nopalina Damanik; Henny Rista; Eka Irawati; Aprisillia Tarigan; Zulkarnaen Batubara (International Journal of Health and Medicine, 2025)
Febrile seizures are a common neurological condition occurring in children aged 6 months to 5 years, with an incidence rate of 2-5%. Prompt and appropriate management is crucial to prevent long-term developmental impacts. This study aims to analyze the relationship between the classification of febrile seizures and child development in the working area of the Barus Jahe Health Center, Barus Jahe District, Karo Regency, North Sumatra Province, in 2023. The research used an observational method with a qualitative descriptive design, collecting data through interviews and physical measurements from 10 children who experienced seizures. The results showed that 70% of the children who experienced seizures were older than 1 year, while 30% were under 1 year old. In terms of gender, 60% of the children were male and 40% were female. Regarding seizure classification, 70% of the children had simple seizures, and 30% had complex seizures. Concerning child development, 60% showed normal development, 20% showed questionable development, and 20% required further monitoring. This study highlights the importance of appropriate management to prevent developmental issues resulting from febrile seizures.